The variable coefficient thin obstacle problem: Carleman inequalities - Koch, Herbert; Rüland, Angkana; Shi, Wenhui (Arxiv, 2015)
In this article we present a new strategy of addressing the (variable coefficient) thin obstacle problem. Our approach is based on a (variable coefficient) Carleman estimate. This yields semi-continuity of the vanishing order, lower and uniform upper growth bounds of solutions and sufficient compactness properties in order to carry out a blow-up procedure. Moreover, the Carleman estimate implies the existence of homogeneous blow-up limits along certain sequences and ultimately leads to an almost optimal regularity statement. As it is a very robust tool, it allows us to consider the problem in the setting of Sobolev metrics, i.e. the coefficients are only $W^{1,p}$ regular for some $p>n+1$. These results provide the basis for our further analysis of the free boundary, the optimal ($C^{1,1/2}$-) regularity of solutions and a first order asymptotic expansion of solutions at the regular free boundary which is carried out in a follow-up article in the framework of $W^{1,p}$, $p>2(n+1)$, regular coefficients.
Last revised 29 May 2015 (v2)
Gesehen am 27.05.2021